2020
DOI: 10.3167/reco.2020.100205
|View full text |Cite
|
Sign up to set email alerts
|

Víctimas de homicidio en el sureste mexicano 2010–2017

Abstract: *Full article is in SpanishEnglish abstract: Homicide is a demographic, social, economic, legal, health problem that affects the quality of life of the population, erodes the economy and citizen security, causes fear and generates impunity. The main victims in Mexico are young people and this research focuses on the integrated southeast including five states: Campeche, Chiapas, Quintana Roo, Tabasco and Yucatán. This research addresses the phenomenon in question, the variations in 2010-2017 homicide rates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The national wealth that this created has been documented above. Development, however, has been accompanied by increasing social divisions, widespread violence and territorial inequities (Pardo Montaño & Dávila Cervantes, 2020; Yanes Pérez et al, 2020). In order to address these challenges, Mexico's legislative framework focuses heavily on the social dimension of sustainable development.…”
Section: Discussion: Normative Mainstreaming As a Key To “Greening” S...mentioning
confidence: 99%
See 1 more Smart Citation
“…The national wealth that this created has been documented above. Development, however, has been accompanied by increasing social divisions, widespread violence and territorial inequities (Pardo Montaño & Dávila Cervantes, 2020; Yanes Pérez et al, 2020). In order to address these challenges, Mexico's legislative framework focuses heavily on the social dimension of sustainable development.…”
Section: Discussion: Normative Mainstreaming As a Key To “Greening” S...mentioning
confidence: 99%
“…Recent studies (Galán Castro et al, 2021; Häbel & Hakala, 2021) have shown how securitization processes, which define traditionally non‐security issues in security terms, undermine sustainability strategies. Second, security is a priority issue in Mexico where drug‐related violence, organized crime and femicides have dominated the political agenda for over a decade (Yanes Pérez et al, 2020). Insecurity is so prominent that it cannot simply be integrated elsewhere in Mexican sustainability discussions as it is a priority policy sector.…”
Section: Methodsmentioning
confidence: 99%